Phytochemical Characterization and Evaluation of Antioxidant Activity in Sorghum bicolor Leaves Extracts - Clark, Poro David; Ndukwe, Gloria Ihuoma; Awatefe, Kehinde Jonathan (Sciences of Phytochemistry, 2026)
This study investigated the phytochemical composition and in-vitro antioxidant potential of leaves extracts from Sorghum bicolor, which were obtained through sequential maceration with solvents of different polarities (n-hexane and methanol). The extraction yields revealed a predominance of polar compounds, with methanol extract (12.5% w/w) significantly higher than the n-hexane extract (1.7% w/w). Gas chromatography–mass spectrometry (GC–MS) profiling, using NIST library matching (similarity scores >80%) without reference standards, showed distinct patterns based on solvent use: the n-hexane extract contained nine primarily lipophilic compounds, mainly consisting of Z-2-octadecen-1-ol and octadecenoic acid derivatives, whereas the methanol extract yielded fifteen characterized by polar fatty acids and oxygenated derivatives. Identifications were tentative; those with lower match scores or inconsistent retention times required confirmation through alternative methods. Antioxidant capacity was evaluated via 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging, hydroxyl radical inhibitory activity (HRIA), and ferric reducing antioxidant power (FRAP) assays. The methanol extract demonstrated concentration-dependent DPPH scavenging (IC₅₀ = 0.1402 mg/L), comparable to vitamin C (0.1369 mg/L) in this assay, while the n-hexane extract showed weaker activity (IC₅₀ 3.22 mg/L). In HRIA and FRAP assays, vitamin C consistently showed greater activity than either extract, with n-hexane IC50 estimates constrained by poor curve fits (R2<0.9). Overall, the methanol extract surpassed the n-hexane extract across all assays but did not match the effectiveness of vitamin C. These in-vitro results suggest that S. bicolor leaves contain polar phytochemicals that merit further fractionation, compound-level characterization, and evaluation in biologically relevant models to elucidate their potential as sources of natural antioxidants.